Nasal hyperreactivity and inflammation in allergic rhinitis - I. M. Garrelds; C. de Graaf-in't Veld; R. Gerth van Wijk; F. J. Zijlstra (Hindawi Limited, 1996)
The history of allergic disease goes back to 1819, when Bostock described his own 'periodical affection of the eyes and chest', which he called 'summer catarrh'. Since they thought it was produced by the effluvium of new hay, this condition was also called hay fever. Later, in 1873, Blackley established that pollen played an important role in the causation of hay fever. Nowadays, the definition of allergy is 'An untoward physiologic event mediated by a variety of different immunologic reactions'. In this review, the term allergy will be restricted to the IgE-dependent reactions. The most important clinical manifestations of IgE-dependent reactions are allergic conjunctivitis, allergic rhinitis, allergic asthma and atopic dermatitis. However, this review will be restricted to allergic rhinitis. The histopathological features of allergic inflammation involve an increase in blood flow and vascular permeability, leading to plasma exudation and the formation of oedema. In addition, a cascade of events occurs which involves a variety of inflammatory cells. These inflammatory cells migrate under the influence of chemotactic agents to the site of injury and induce the process of repair. Several types of inflammatory cells have been implicated in the pathogenesis of allergic rhinitis. After specific or nonspecific stimuli, inflammatory mediators are generated from cells normally found in the nose, such as mast cells, antigen-presenting cells and epithelial cells (primary effector cells) and from cells recruited into the nose, such as basophils, eosinophils, lymphocytes, platelets and neutrophils (secondary effector cells). This review describes the identification of each of the inflammatory cells and their mediators which play a role in the perennial allergic processes in the nose of rhinitis patients.